Pengawasan Manajemen Meritokrasi Dalam Pengelolaan Aparatur Sipil Negara Di Bagian Umum Sekretariat Daerah Kota Baubau - Dahlan Dahidu; Andi Tenri; Zainul Abidin (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study aims to analyse meritocratic management oversight in the administration of the Civil Service (ASN) within the General Affairs Division of the Baubau City Regional Secretariat. The study employs a qualitative approach using a case study methodology. Data were collected through in-depth interviews, observation and document analysis. Data analysis utilised the interactive model proposed by Miles, Huberman, and Saldaña. The findings indicate that meritocratic management oversight within the General Affairs Division of the Baubau City Regional Secretariat is not yet functioning optimally, as internal oversight remains focused on administrative compliance rather than substantive control based on competence and performance. Performance appraisals of ASN have not yet fully served as the basis for promotion, transfer, and career development. Furthermore, reward and punishment mechanisms have not been consistently applied, leading to weak motivation among civil servants and creating scope for subjectivity in personnel decision-making. This study confirms that the failure of the merit system at the local level is not solely due to weak regulations, but rather to the weakness of managerial oversight functions in ensuring the consistent implementation of the merit system.